2012
DOI: 10.1186/1478-811x-10-5
|View full text |Cite
|
Sign up to set email alerts
|

Actin-dependent activation of serum response factor in T cells by the viral oncoprotein tip

Abstract: Serum response factor (SRF) acts as a multifunctional transcription factor regulated by mutually exclusive interactions with ternary complex factors (TCFs) or myocardin-related transcription factors (MRTFs). Binding of Rho- and actin-regulated MRTF:SRF complexes to target gene promoters requires an SRF-binding site only, whereas MAPK-regulated TCF:SRF complexes in addition rely on flanking sequences present in the serum response element (SRE). Here, we report on the activation of an SRE luciferase reporter by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Interestingly, we found that targeting Src using dasatinib was associated with decreased SRF which suggests that Src may transcriptionally regulates αSMA synthesis. In light of this finding, a study conducted in T-cells demonstrated that Src activation is necessary for the induction of SRF and transcriptional regulation of target genes (Katsch et al, 2012). Further studies are necessary to examine the Src-mediated transcriptional regulation in myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that targeting Src using dasatinib was associated with decreased SRF which suggests that Src may transcriptionally regulates αSMA synthesis. In light of this finding, a study conducted in T-cells demonstrated that Src activation is necessary for the induction of SRF and transcriptional regulation of target genes (Katsch et al, 2012). Further studies are necessary to examine the Src-mediated transcriptional regulation in myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Data represent the percentage of n = 51 sections (from three to four embryos). ( e ) HH11–12 embryos were electroporated in ovo with shCtrl or shEZH2 together with pSRE-luc plasmid [ 24 26 ] and β-gal reporter used as internal control; 48 h PE the neural tubes were dissected out, the tissue was disaggregated and the luciferase activity measured using the Life Technologies dual kit. Data represent mean of three experiments from five to seven embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Although these aspects of actin dynamics are incompletely understood and notoriously difficult to visualize, even less is known about usurpation of them by virions. Nevertheless, several indications for the participation of these cellular processes in virion production/assembly have emerged .…”
Section: Actin and The Viral Life Cyclementioning
confidence: 99%